Kultur produzieren künstlerische Praktiken und kritische kulturelle Produktion - Zobl, Elke 1975-; Klaus, Elisabeth 1955-; Moser, Anita; Baumgartinger, Persson Perry 1976-; Bleuler, Marcel 1980-; Drüeke, Ricarda 1976-; Frketić, Vlatka; Smodics, Elke (transcript Verlag, 2019)
The volume collects key concepts in the context of intervening and participatory artistic practices and provides insight into theoretical perspectives and artistic-cultural implementations
Keywords: Cultural Studies; DIY.; Intervention; Kultur; Kulturarbeit; Kulturmanagement; Kulturtheorie; Kulturvermittlung; Kulturwissenschaft; Kunst; Kunstwissenschaft; Migrationsgesellschaft; Partizipation; Politische Kunst; Zeitgenössische Kunst; Öffentlichkeiten; SOCIAL SCIENCE / Popular Culture; Kulturwissenschaften; Beteiligung; Öffentlichkeit; Migration; Aufsatzsammlung